Individual-psychological factors and perception of social support in burnout syndrome - Jovanović, Vesna R.; Hinić, Darko; Džamonja Ignjatović, Tamara; Stamatović Gajić, Branka; Gajić, Tomislav; Mihajlović, Goran (Vojnosanitetski pregled, 2021)
Background/Aim. Burnout syndrome is a psychological phenomenon that occurs as a response to chronic interpersonal stressors at work. It is manifested by emotional exhaustion, depersonalization and a sense of reduced personal accomplishment. The aim of the study was to examine the correlation between burnout syndrome, individual-psychological factors and social support among special and regular education teachers, as well as to determine differences of burnout syndrome dimensions between groups of teachers with different educational backgrounds. Methods. This non-experimental, cross-sectional correlation study included 317 teachers (122 special education teachers and 38 other teachers in special education for children with intellectual disabilities and 157 teachers from regular primary schools) from Belgrade. Maslach Burnout Inventory (MBI), Assertiveness Assessment Questionnaire Scale (A-Scale), Rosenberg Self-Esteem Scale (RSS), Teacher Self-Efficacy Scale (TSES), and Multidimensional Perceived Social Support Scale (MSPSS) were used in the study. Results. The highest prevalence of high levels of burnout were recorded on the emotional exhaustion subscale and were 38% for special education teachers, 47% for other teachers in special education, and 39% for teachers in regular education. The most important predictors of burnout in special education teachers were: for emotional exhaustion (self-esteem, efficiency of class management and seniority); for depersonalization (self-esteem, efficiency of class management and social support); for a sense of lower personal accomplishment (assertiveness, effective student learning and class management). The most important predictors of burnout in regular education teachers were: for emotional exhaustion (assertiveness, effective class management, social support and seniority); for depersonalization (self-esteem, effective student learning and seniority); for a reduced personal accomplishment (self-esteem, effective student learning and social support). Conclusion. Individual-psychological factors have emerged as an important predictor of burnout syndrome in the teaching profession, indicating the importance of examining the impact of these factors in other professions that are characterized by the specific demands for a deeper emotional investment during the work process.